2012
DOI: 10.1002/hbm.22083
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution track-density imaging of thalamic substructures: Comparison with high-resolution anatomical magnetic resonance imaging at 7.0T

Abstract: The thalamus is one of the most important brain structures, with strong connections between subcortical and cortical areas of the brain. Most of the incoming information to the cortex passes through the thalamus. Accurate identification of substructures of the thalamus is therefore of great importance for the understanding of human brain connectivity. Direct visualization of thalamic substructures, however, is not easily achieved with currently available magnetic resonance imaging (MRI), including ultra-high f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 32 publications
2
50
0
Order By: Relevance
“…We compared DEC stTDI maps with conventional T 2 * images, diffusion tensor based images (DEC FA), and histological sections to demonstrate the efficacy of DEC stTDI maps for neuroanatomical characterization of the zebrafish brain. The structures visualized in the DEC stTDI maps were consistent with our histological analysis, supporting the veracity of the anatomical contrast in these maps, which is in agreement with previous TDI studies in the mouse (Calamante et al 2012b) and human (Calamante et al 2012a) brains. Moreover the super-resolution property and the local-directional information provided by DEC stTDI, combined with the high signal to noise ratio provided by ultra-high MRI at 16.4T, enabled enhanced examination of the zebrafish brain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We compared DEC stTDI maps with conventional T 2 * images, diffusion tensor based images (DEC FA), and histological sections to demonstrate the efficacy of DEC stTDI maps for neuroanatomical characterization of the zebrafish brain. The structures visualized in the DEC stTDI maps were consistent with our histological analysis, supporting the veracity of the anatomical contrast in these maps, which is in agreement with previous TDI studies in the mouse (Calamante et al 2012b) and human (Calamante et al 2012a) brains. Moreover the super-resolution property and the local-directional information provided by DEC stTDI, combined with the high signal to noise ratio provided by ultra-high MRI at 16.4T, enabled enhanced examination of the zebrafish brain.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated the utility of DEC stTDI for visualization of small brain structures, such as the thalamic nuclei (Calamante et al 2012a), the cerebellar peduncles , and other structures in the human brain (Cho et al 2013). By registering the TDI data to other MR images and histology, more detailed highresolution atlases could be created, due to the complementary information of all these imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Our TDI maps for adult barreloids were consistent with that seen in early rodent brain development, and highlight the advantage of the 3D TDI method to allow "virtual" slicing, overcoming the constraints of irreversible tissue sectioning used in histology. Overall, the MRI diffusion micro-imaging was necessary to resolve thalamic structures in mice (20μm spatial resolution for mice) compared to 200μm spatial resolution for humans (Calamante et al, 2012a); future studies are warranted to create detailed parcellation of thalamic sub-structures in mice based on connectivity pattern (Behrens et al, 2003;Calamante et al, 2012a).…”
Section: Thalamic Substructures -Vpm Barreloidsmentioning
confidence: 99%
“…Diffusion MRI is an important mapping tool for tissue structure and connectivity, including information about fibre orientation and integrity and has been used to visualize tissue microstructure in humans and animal models (Behrens et al, 2003;Calamante et al, 2012a;Calamante et al, 2010;Jiang and Johnson, 2011;Kim et al, 2012;Moldrich et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a different way, a new concept of the SR problem for DW imaging has been proposed in (Calamante et al, 2012a;Calamante et al, 2010;Calamante et al, 2012b;Nedjati-Gilani et al, 2008). Instead of increasing image resolution, the authors proposed to reconstruct a HR density map by using the extra information resulting from tractography.…”
Section: Introductionmentioning
confidence: 99%